PELATIHAN IDENTIFIKASI FORMALIN DAN BORAKS PADA MAKANAN SECARA SEDERHANA DI KELURAHAN PAMIJEN KABUPATEN BANYUMAS - Adita Silvia Fitriana; Sri Royani (Universitas Pancasila, 2021)
Formalin and borax are dangerous chemicals that are often misused as food preservatives. Various inspections have been carried out to minimize the use of formalin and borax in food, but there are still many formalin and borax in foods. The community, especially housewives, should have the ability to identify the presence of formalin and borax in food in order to protect family members from the exposure of those chemicals. Housewives in Pamijen Sub-District do not have knowledge and skills to identify formalin and borax content in food yet. Through this community service program, housewives in Pamijen Sub-District are expected to be able to test formalin and borax content in food independently. The program began with counseling about the food characteristics that contains formalin and borax; and the impact on health. This program continued with training on how to identify and practicing on how to detect formalin and borax in some food samples with a simple and an easy method. The results indicate that this program can increase patricipants’ knowledge about formalin and borax; and skills to identify them. Keywords: preservatives, formalin, borax, food